2016
DOI: 10.3174/ajnr.a4952
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Deep Gray Matter Nuclei Atrophy Is Relevant for Explaining Cognitive Impairment in MS: A Multicenter Study

Abstract: BACKGROUND AND PURPOSE:The structural MR imaging correlates of cognitive impairment in multiple sclerosis are still debated. This study assessed lesional and atrophy measures of white matter and gray matter involvement in patients with MS acquired in 7 European sites to identify the MR imaging variables most closely associated with cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 37 publications
11
64
2
6
Order By: Relevance
“…Our results are in line with prior studies that assessed cognition in MS patients and observed stronger decline in males (Lin et al, 2016;Schoonheim et al, 2012), which moreover was related to EDSS scores (Savettieri et al, 2004). In our cohort, better performance in the TMT-B was further associated to higher deep gray matter volume in our regions of interest, again in accordance with previous research (Damjanovic et al, 2017;Modica et al, 2016;Schoonheim et al, 2012). The less complex TMT-A is potentially too insensitive to reflect initial variations in gray matter integrity or network configurations but might be more suitable to distinguish patients of different disease stages.…”
Section: Structural Integrity and Cognitive Performancesupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with prior studies that assessed cognition in MS patients and observed stronger decline in males (Lin et al, 2016;Schoonheim et al, 2012), which moreover was related to EDSS scores (Savettieri et al, 2004). In our cohort, better performance in the TMT-B was further associated to higher deep gray matter volume in our regions of interest, again in accordance with previous research (Damjanovic et al, 2017;Modica et al, 2016;Schoonheim et al, 2012). The less complex TMT-A is potentially too insensitive to reflect initial variations in gray matter integrity or network configurations but might be more suitable to distinguish patients of different disease stages.…”
Section: Structural Integrity and Cognitive Performancesupporting
confidence: 93%
“…However, since males are less frequently, but more severely affected by the disease (Greer & McCombe, 2011), an adverse effect of gender on both physical disability and cognitive scores was not unexpected. In our cohort, better performance in the TMT-B was further associated to higher deep gray matter volume in our regions of interest, again in accordance with previous research (Damjanovic et al, 2017;Modica et al, 2016;Schoonheim et al, 2012). Our results are in line with prior studies that assessed cognition in MS patients and observed stronger decline in males (Lin et al, 2016;Schoonheim et al, 2012), which moreover was related to EDSS scores (Savettieri et al, 2004).…”
Section: Structural Integrity and Cognitive Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…MS-related cognitive impairment has been associated with both cortical (Benedict, 2002; Benedict et al, 2005; Morgen et al, 2006) and subcortical (Houtchens et al, 2007; Sicotte et al, 2008; Batista et al, 2012; Damjanovic et al, 2016; Preziosa et al, 2016; Rocca et al, 2016) gray matter atrophy and cortical lesions (Calabrese et al, 2009) explaining between 20 and 60% of the variance of a variety of cognitive tests assessing the most commonly affected cognitive domains using multilinear models.…”
Section: Neuro-anatomymentioning
confidence: 99%
“…Indeed, it is increasingly recognized that pathology in the gray matter including the cortex is central to the progression of MS (Calabrese et al, 2015;Mahad et al, 2015;Ontaneda et al, 2017). Gray matter pathology correlates with accruing disability, predicts conversion to progressive MS 10 and explains the increasing cognitive deficits that MS patients with advanced disease experience (Damjanovic et al, 2017;Eshaghi et al, 2018;Ontaneda et al, 2017;Scalfari et al, 2018). Despite this profound clinical importance, our understanding of the mechanisms underlying cortical pathology in progressive MS remains poor, in part because modelling gray matter inflammation has been difficult.…”
Section: Introductionmentioning
confidence: 99%